Ghrelin in Senegalese sole (Solea senegalensis) post-larvae: Paracrine effects on food intake - Navarro-Guillén, Carmen (2019)
Successful food consumption and digestion depend on specifics anatomical and behavioral characteristics and corresponding physiological functions that should be ready to work at the appropriate time. The physiological regulation of appetite and ingestion involves a complex integration of peripheral and central signals by the brain. Ghrelin is a peptide hormone involved in the control of energy homeostasis and increases food intake in mammals, however ghrelin has species-specific actions on food intake in fish. The aim of this study was to investigate whether this peptide has an orexigenic or anorexigenic role in Senegalese sole (Solea senegalensis) in order to improve the knowledge of the physiological basis underlying feeding activity. Feed intake was measured at several sampling points to determine the overall action time of the peptide and its effect in Senegalese sole food intake. Artemia protein digestibility and retention were determined in order to analyze the ghrelin effect in fed and fasted Senegalese sole post-larvae. Results suggested that ghrelin acts as orexigenic hormone in Senegalese sole, with a response time around 25 min. Results indicated that Senegalese sole post-larvae are able to maintain absorption and retention capacities independently of feeding rate and nutritional status. Furthermore, the present study gives insight for the first time of the fate of the retained amino acids, being mainly used for protein accretion (86.79% of retained amino acids recovered in protein and FAA fractions). (C) 2016 Elsevier Inc. All rights reserved.